1978
DOI: 10.1113/jphysiol.1978.sp012386
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain‐sensitive fluid accumulation and ion transport by rabbit blastocysts.

Abstract: SUMMARY1. By incubating 6-day post-coitum (p.c.) blastocysts in medium supplemented with either 20 mm-sucrose or 10 mM-KCl it was possible to show that the trophectoderm of the blastocyst prevents the concentration of K in the blastocoele fluid rising to external concentrations.2. The concentrations of K in the blastocoele fluid are maintained predominantly by leakage of K from the trophoblast cells into the blastocoele and by ouabainsensitive transport of K into the trophoblast cells from the blastocoele flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Formation of tight junctions and adherens junctions including binding of the catenin-cadherin complex to actin cytoskeleton is necessary for polarization of blastomeres in morula stage embryos and is a prerequisite for formation of the blastocyst [25]. The polarized trophectoderm can engage in active transport of water and select nutrients into the blastocoel [26,27].…”
Section: The Uterine Lumenal Microenvironment Derives From the Secretmentioning
confidence: 99%
“…Formation of tight junctions and adherens junctions including binding of the catenin-cadherin complex to actin cytoskeleton is necessary for polarization of blastomeres in morula stage embryos and is a prerequisite for formation of the blastocyst [25]. The polarized trophectoderm can engage in active transport of water and select nutrients into the blastocoel [26,27].…”
Section: The Uterine Lumenal Microenvironment Derives From the Secretmentioning
confidence: 99%
“…The appearance of the Chloride channels in the mouse conceptus voltage-inactivated Cl K conductance was associated with the emergence of this trophoblast lineage (Johnson 1986(Johnson , 2009, suggesting a role for this conductance in the vectorial movement of electrolytes and water into the blastocoel cavity. Expansion of the blastocoel cavity in the mouse blastocyst requires extracellular Cl K , is dependent on both paracellular and transcellular movement of Cl K across the TE (Manejwala et al 1989, Brison & Leese 1993, Zhao et al 1997, and is driven by the basolaterally localized Na 1977, Biggers et al 1978, Watson & Kidder 1988. In this study, DIDS did not completely prevent blastocyst expansion, as observed previously (Zhao et al 1997), an observation that suggested a role for other pathways for Cl K movement such as the paracellular pathway or the DIDS-insensitive, voltage-inactivated current described here.…”
Section: Discussionmentioning
confidence: 99%
“…For example, net transtrophectodermalNa+ influx increases 10-fold during this period (Borland etal,\ 976). Ouabain, a specific inhibitor of Na+/K + ATPase, has been shown to inhibit both the accumulation of blastocyst fluid (Biggers et al, 1978) and > 50% of net trans-trophectodermal Na+ transport in preimplantation rabbit blastocysts (Benos, 1981b).…”
Section: Free Intracellular Methionine Contentmentioning
confidence: 99%
“…Mechanisms of active transepithelial solute transport have been reported to mediate this process of blastocoele expansion (see Benos & Biggers, 1981;Benos et al, 1985, for reviews). Specifically, there is increasing evidence that the ubiquitous membrane-bound enzyme Na + /K+ ATPase (EC 3.6.1.3) mediates transtrophectodermal fluid transport in the preimplantation mammalian blastocyst (Biggers et al, 1978).…”
Section: Introductionmentioning
confidence: 99%